Senam Kaki Sebagai Upaya Pencegahan Diabetic Foot pada Penderita Diabetes Mellitus Tipe 2 - Muhsinin, Siti Zuraida; Pujiningsih, Erniawati; Sulastien, Herni; Hadi, Sofian; Musniati, Musniati; Safitri, Saitun (Idea Pengabdian Masyarakat, 2023)
Nurses are one of the health teams whose role is to help DM sufferers to prevent diabetic foot, one of which is by teaching DM sufferers to do foot exercises. Foot exercise is an activity or physical exercise performed by patients with diabetes mellitus by moving their feet. One of the goals is to help improve blood circulation in the legs, to prevent diabetic ulcer. Community service activities with the theme "foot exercise as an effort to prevent diabetic foot in people with type 2 diabetes mellitus" have been carried out in collaboration with the Prolanis team at the Karang Pule Health Center in Mataram. The method used is education, demonstration, and then all participants practice how to do leg exercises. This activity was carried out as a concrete manifestation of the involvement of nurses in efforts to prevent diabetic foot in patients with type 2 DM. From this activity, it can be concluded that all participants could practice how to do foot exercises and they were active and enthusiastic about participating in all activities until the end. Based on the explanation above, it is necessary to carry out periodic foot exercise activities and monitor/examine ABI in an effort to prevent diabetic foot complications in type 2 DM patients.